Masters, servants, and magistrates in Britain and the Empire, 1562-1955 - Hay, Douglas; Craven, Paul, 1950- (Studies in legal history., 2004)
Master and servant acts, the cornerstone of English employment law for more than four hundred years, gave largely unsupervised, inferior magistrates wide discretion over employment relations, including the power to whip, fine, and imprison men, women, and children for breach of private contracts with their employers. The English model was adopted, modified, and reinvented in more than a thousand colonial statutes and ordinances regulating the recruitment, retention, and discipline of workers in shops, mines, and factories; on farms, in forests, and on plantations; and at sea. This collection p.